A molecular phylogeny of East African Amytta (Orthoptera: Tettigoniidae, Meconematinae) with data on their cytogenetics. (4th October 2017) - HEMP, CLAUDIA; HELLER, KLAUS‐GERHARD; WARCHAŁOWSKA‐ŚLIWA, ELŻBIETA; GRZYWACZ, BEATA
Abstract: This is the first study to address the molecular phylogeny of East African Meconematinae. We used DNA sequence data from the three genes cytochrome oxidase subunit I ( COI ), 16S rRNA and histone H3 to reconstruct the relationships within the genus Amytta using Bayesian Inference and maximum likelihood. We included 45 individuals representing 19 Meconematinae taxa from Africa, Europe and Australia, and three outgroup species to explore taxonomic limits at different levels. Members of the genus Amytta belong to three related lineages within Meconematinae. Species of Amytta were found to be monophyletic with Meconema and Phlugidia as sister groups. The molecular results are in accordance with previous morphological and ecological studies. Chromosome numbers and the type of sex determination systems found in Amytta agrees with the three lineages also found in the phylogenetic tree. We conclude that the radiation of Amytta species is geological young. Biogeographical patterns caused by climatic fluctuations of the past seen also in other nonrelated Orthoptera taxa such as the coptacrine genus Parepistaurus are the drivers of biodiversity in the area. Abstract : This is the first study to address the molecular phylogeny of East African Meconematinae using the three genes cytochrome oxidase subunit I ( COI ), 16S rRNA and histone H3 . Forty five individuals representing 19 Meconematinae taxa from Africa, Europe and Australia were analysed. The molecular results are in accordance with previous morphological and ecological studies. Biogeographical patterns caused by climatic fluctuations of the past seen also in other nonrelated Orthoptera taxa are the drivers of biodiversity in the area.